The grand cycle of conjuring treatises: Modern Magic, More Magic, Later Magic and Latest Magic. Issue 2 (3rd April 2018) - Houstoun, William George Provan
ABSTRACT: Angelo Lewis's Modern Magic, 1876, is a keystone text in the history of conjuring, a book that attempted to teach the reader how to become a magician rather than simply telling them how tricks were done. It was followed by three further publications, More Magic, Later Magic and Latest Magic that together form a body of work that spans magic's Golden Age. This article uses archival materials, such as Lewis's personal notebooks and his publisher's records, as well as little-known specialist literature produced for magicians, to trace a shift of perspective in Lewis's writing on conjuring. Examining Lewis's sources, the four books' critical reception from both magicians and the public, and the details of their publication, I will show that Lewis's career began with him writing for the public from the perspective of the amateur magician and ended with him deeply embedded in the world of conjuring, writing primarily for other magicians.